Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T19:47:29+01:00
A) 1/3x - 2 = x + 2
x-x=2-2-1/3
0=-1/3

b) 1 - 6/7x = 4/7
x= 4/7+6/7-1
x=3/7
c) 6(1/4x - 2) = 18
1 2/4x= 18-12
1 2/4x= 2 /: 6/4
x= 1 2/6
d) x/6 - 1/6 = 1

e) -2(2x - 1) = x/3
f) 2/5(3 - x) = -2
g) 3/4(2 - 3x) = -6
h) 1/5(x - 3) = 9 - x
i) 0,6 + x/2 = x + 1
1 1 1
2010-03-14T19:49:02+01:00
A) 1/3x - 2 = x + 2 = 1\3x-x=-2-2= 1\3=-4\

b) 1 - 6/7x = 4/7

c) 6(1/4x - 2) = 18

d) x/6 - 1/6 = 1

e) -2(2x - 1) = x/3

f) 2/5(3 - x) = -2

g) 3/4(2 - 3x) = -6

h) 1/5(x - 3) = 9 - x

i) 0,6 + x/2 = x + 1